Genetic parameter estimation for growth traits in males of Karan fries cattle - AHMAD, TAVSIEF; MAGOTRA, ANKIT; GUPTA, A K; DASH, SHAKTI KANT; MOHSIN, MIR; SHABIR, MIR; HAMADANI, AMBREEN; YADAV, B R (The Indian Journal of Animal Sciences, 2021)
The significance of sire selection in the herd is reflected by the total genetic gain through sire-to-sire and sireto- dam pathways contributing greater than 50% contribution. The present investigation was carried out to estimate genetic parameters of males of Tharparkar (TP) and Karan-Fries (KF) cattle. Data on body weights of Tharparkar and Karan Fries males born during the period 199-2012 at ICAR-National Dairy Research Institute (ICAR-NDRI), Karnal, India were utilized in the present study. The genetic and phenotypic correlations among different body weights were estimated from the analysis of variance and covariance among sire groups. Paternal half-sib correlation method was used to estimate heritability of growth traits. Heritability estimates in KF were found to be of moderate to high magnitude, as 0.23±0.06, 0.43±0.10, 0.28±0.10, 0.36±0.11, 0.39±0.12, 0.38±0.14, 0.27±0.19 for weight at birth and weight at monthly interval up to six months, respectively. Genetic and phenotypic correlations were found to vary from moderate to high among the traits. Our study revealed that the magnitude of heritability indicates a high scope of further improvement in Karan Fries. Selective breeding and positive genetic correlations should be considered while designing selection programs.